2020
DOI: 10.1007/978-3-030-49932-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Autism Serious Game Framework (ASGF) for Developing Games for Children with Autism

Abstract: Masters of Science in Computer Science Thesis title: Autism Serious Game Framework (ASGF) for Developing Games for Children with Autism An oral defense of this thesis took place on December 2, 2019 in front of the following examining committee:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…According to Ghanouni, et al [80], motion gaming programmes like Kinect are able to facilitate children with autism in learning to create a repertoire of internal models through NUIs. For example, combining RGB cameras, depth detection, and careful user interface design in the Kinect visual sensor would provide better gaming and enjoyment experiences [62]. As a result, this study found that interactions play an important role in catering to the needs of children with autism.…”
Section: Game Elementsmentioning
confidence: 84%
“…According to Ghanouni, et al [80], motion gaming programmes like Kinect are able to facilitate children with autism in learning to create a repertoire of internal models through NUIs. For example, combining RGB cameras, depth detection, and careful user interface design in the Kinect visual sensor would provide better gaming and enjoyment experiences [62]. As a result, this study found that interactions play an important role in catering to the needs of children with autism.…”
Section: Game Elementsmentioning
confidence: 84%
“…After the compilation of research, there is a heterogeneity between the different fields of study observed, although there is a greater predominance of research on design and focused on the design and testing of prototypes. In terms of design (35%), Gaudi et al ( 2020 ) create the ASGF interface to develop interventions with SG in therapeutic sessions. In the same line, Jaramillo et al ( 2022 ) establish the criteria to evaluate the usability and accessibility of the SG.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, both the use of gamified environments and SG allow to increase their motivation in therapeutic sessions, managing to improve long-term behaviors (Malinverni et al, 2017 ; Van Dooren et al, 2019 ). Specifically, Gaudi et al ( 2020 ) consider that SG are becoming an effective alternative to traditional therapy, since they allow adaptation to specific needs and individual casuistry by covering a wide range of scenarios and characters.…”
Section: Introductionmentioning
confidence: 99%